Rancang Bangun Mesin Pemotong Tahu dengan Pendekatan Antropometri untuk Meningkatkan Produktivitas Produksi Tahu (Studi Kasus: UD Mardi Mulyo) - Gahara Suttan Babadi Mubarok; Jaka Purnama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD Mardi Mulyo is a small-medium tofu enterprise in Wringinanom, Gresik, East Java, producing up to 5,000 pieces of tofu per day with 8 workers in 10 working hours. The main problem is manual tofu cutting using a knife, requiring an average of 10 minutes per cooking cycle (15 kg soybean), causing physical fatigue, inconsistent cutting sizes, and inability to meet market demand. This study designed and built a pneumatic electric tofu cutting machine based on seated operator anthropometric data. Methods included field observation, stopwatch time study, anthropometric measurement, percentile calculation, and financial feasibility analysis. The machine (60×60×130 cm) uses a double-acting pneumatic cylinder Ø50 mm, food-grade SUS 304 stainless steel, costs Rp 7,100,000, with a Payback Period of ±2.39 months. The machine reduces cutting time by 50% and significantly improves cutting size consistency.